2010
DOI: 10.21161/mjm.20109
|View full text |Cite
|
Sign up to set email alerts
|

Studies on nodulation, biochemical analysis and protein profile ofRhizobium isolated from Indigofera species

Abstract: Nodulation characteristics in five species of Indigofera viz., I .trita, I. linnaei, I. astragalina, I. parviflora and I. viscosa was studied at regular intervals on the plants raised in garden soil. Among the species studied, highest average number of nodules per plant of 23 with maximum sized nodules of 8.0 mm diameter was observed in I. astragalina. Biochemical analysis of root nodules of I. astragalina revealed that the leghaemoglobin content of nodules and nitrogen content of root, shoot, leaves and nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Previous studies observed EI values of 3.1 for cowpea rhizobial isolates (Oliveira et al, 2006b) and values of up to 3.5 for fast-growing isolates from pigeonpea (Cajanus cajan) (Fernandes Júnior et al, 2012). Kumari et al (2010) reported the importance of the enzymes urease, protease, amylase, and gelatinase in the formation of nodules, stating that rhizobia that produce these enzymes are considered more effective in nodulation and N fixation.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies observed EI values of 3.1 for cowpea rhizobial isolates (Oliveira et al, 2006b) and values of up to 3.5 for fast-growing isolates from pigeonpea (Cajanus cajan) (Fernandes Júnior et al, 2012). Kumari et al (2010) reported the importance of the enzymes urease, protease, amylase, and gelatinase in the formation of nodules, stating that rhizobia that produce these enzymes are considered more effective in nodulation and N fixation.…”
Section: Resultsmentioning
confidence: 97%
“…The EPS produced by the bacteria helps fix atmospheric nitrogen by lowering the high oxygen pressure (Kumari et al, 2009), and it also works to change the form of Rhizobium bacteria from the stick form to the form of nitrogen-fixing known as Bacteroids within the root nodules of host plants (Fraysse et al, 2003).…”
Section: Science Archives (Issn:2582-6697)mentioning
confidence: 99%
“…A gelatine test is conducted by inoculating the rhizobia in a gelatine medium. The degradation of the medium is an indication of the presence of a gelatinase enzyme in the rhizobia (Kumari et al, 2010;Tyagi et al, 2017;Qudratullah Oryakhil, 2020). Production of the gelatinase enzyme by rhizobia is among the features that promote nodulation and N 2 fixation (Kumari et al, 2010;Qudratullah Oryakhil, 2020).…”
Section: Characterization Of Soybean-nodulating Rhizobia Morphologica...mentioning
confidence: 99%
“…The degradation of the medium is an indication of the presence of a gelatinase enzyme in the rhizobia (Kumari et al, 2010;Tyagi et al, 2017;Qudratullah Oryakhil, 2020). Production of the gelatinase enzyme by rhizobia is among the features that promote nodulation and N 2 fixation (Kumari et al, 2010;Qudratullah Oryakhil, 2020). Among the products of gelatine hydrolysis by the gelatinase, enzyme are amino acids and peptides.…”
Section: Characterization Of Soybean-nodulating Rhizobia Morphologica...mentioning
confidence: 99%